How is Implementation Of The AISAS Model In Museum Promotion Through The Website? - Hafsah Nugraha; Angga Hadiapurwa; Dalilah Aliyah Zuhrah (Universitas Sebelas Maret, 2023)
This research is based on the development of information needs and efforts of the museum as one of information institutions to meet these information needs by conveying information in its collections. The information conveyed to relate to aspects of attention, interest, search, action, and share designed in a website-based museum information system. This study aims to describe the results of the implementation of the museum website based on AISAS aspects. The approach used in this research is descriptive quantitative with museum visitors as respondents. The respondents involved were 50 museum visitors, with the criteria determined by the researcher. The data that has been obtained is then processed and analyzed descriptively. The results showed that the overall museum website designs have met the expectations of website visitors to good criteria based on the AISAS aspect, but the action and share indicators are expected to be further improved because they are still in the fairly good category. Based on the results of this study, it is expected that the design of the museum website can pay attention to every indicator in the AISAS aspect so that the museum website can meet the expectations of visitors to the museum website.